Fabrication of an AMC/MMT Fluorescence Composite for its Detection of Cr(VI) in Water - Wei, Yanke; Mei, Lefu; Li, Rui; Liu, Meng; Lv, Guocheng; Weng, Jianle; Liao, Libing; Li, Zhaohui; Lu, Lin (Frontiers in Chemistry, 2018)
Hexavalent chromium species, Cr(VI), activates teratogenic processes, disturbs DNA synthesis and can give rise to mutagenous changes leading to malignant tumors. It is necessary to carry out its detection and quantification. Fluorescence detection by organic dye molecules is a simple and rapid method in pollutant analysis. Its application is limited because of concentration quenching caused by aggregation of fluorescent molecules. In this study, 7-amino-4-methylcoumarin (AMC) was successfully intercalated into the interlayer space of montmorillonite (MMT), which resulted in significant inhibition in fluorescence quenching. With its enhanced fluorescent property, the composite was fabricated into a film with chitosan to detect Cr(VI) in water. Cr(VI) in aqueous solution can be detected by instruments in the range of 0.005 to 100 mM with a detection limit of 5 μM.